Safety and recommendations for vaccinations of children with inborn errors of metabolism. (November 2021) - Hady-Cohen, R.; Dragoumi, P.; Barca, D.; Plecko, B.; Lerman-Sagie, T.; Zafeiriou, D.
Abstract: Inborn errors of metabolism (IEM) are genetic disorders due to a defective metabolic pathway. The incidence of each disorder is variable and depends on the respective population. Some disorders such as urea cycle disorders (UCD) and organic acidurias, pose a high risk for a metabolic crisis culminating in a life-threatening event, especially during infections; thus, vaccines may play a crucial role in prevention. However, there are different triggers for decompensations including the notion that vaccines themselves can activate fever and malaise. Additionally, many of the IEM include immunodeficiency, placing the patients at an increased risk for infectious diseases and possibly a weaker response to immunizations. Since metabolic crises and vaccine regimens intersect in the first years of life, the question whether to vaccinate the child occupies parents and medical staff. Many metabolic experts hesitate to vaccinate IEM patients, disregarding the higher risk from the direct infections. In this paper we summarize the published data regarding the safety and recommendations for vaccinations in IEM patients, with reference to the risk for decompensations and to the immunogenic component. Highlights: Inborn errors of metabolism are genetic disorders due to a flawed metabolic pathway. Some disorders pose a high risk for a metabolic crisis, notably during infections. Vaccinations may play a crucial role in infectious disease control and prevention. Many metabolic experts and parents question when to vaccinate metabolic patients. Here are several recommendations for vaccinations in paediatric metabolic patients.